The high school research initiative prepares and supports Texas science teachers doing research in their classrooms - Buckley, Deanna; Stovall, Gwendolyn; Williams, Bailey; Beckham, Josh; Mishler, Dennis; Ramsey, Mary; Reichler, Stuart; Hutson, Andrea (American Journal of STEM Education, 2025)
Many Texas science teachers, especially in rural areas, lack access to content specific, inquiry-based professional development. To address this, UTeach and the Freshman Research Initiative partnered to create the High School Research Initiative (HRI), offering research-based curricula, training, and classroom support. The HRI leads teachers in a two-week research methods course and provides standard-aligned training in biomedical and behavioral research modules—Fish Behavior, Caffeinated Coli, Habitat Scouts, and Virtual Drug Screening—informed by active university research. Teachers receive lesson plans, activities, and materials to implement the modules in their classrooms. A mixed-methods evaluation revealed increased teacher preparedness, strong community support, and successful classroom integration. This paper outlines the HRIs’ model, highlights its impact, and offers strategies for preparing in-service science teachers.